Perubahan Kurikulum dan Perubahan Perilaku Mengajar Guru - Wendi Rais (LPPM STIE PERTIBA Pangkalpinang, 2019)
National education, as one of the national development sectors in an effort to educate the nation's life, has a vision of the realization of the education system as a strong and authoritative social institution to empower all Indonesian citizens to develop into qualified human beings so that they are able and proactively respond to the challenges of the ever-changing times. Of the many elements of educational resources, the curriculum is one element that can make a significant contribution to realizing the process of developing the quality of potential learners. The curriculum is also a fundamental guideline in the teaching and learning process in the world of education. Success or failure of education, whether or not a student and educator are able to absorb and provide teaching, and success or failure of a goal. If the curriculum is designed systematically and comprehensively and is integral to all the development and learning needs of students to prepare themselves for their lives, of course, the results/outputs of education will be able to realize expectations. But if not, failure after failure will continue to haunt the world of education. The application of quality, effective and efficient curriculum changes requires teachers to be creative in improving classroom management because teachers are role models for all students. In this case the need to change the mindset of teachers so that they are able to become facilitators and learning partners of their students. In addition, a teacher must have an attitude of professionalism in carrying out learning. Teacher professional development can also be done by providing opportunities for teachers to carry out various activities, give advice, admonish, guide, become representatives of schools with extracurricular activities and community activities. A half-hearted educational reform will confuse the real practitioners of education.